Commodity, Trading, and Commerce in the Contemporary Lithuanian Literature - Keturakis, Saulius (Respectus Philologicus, 2015)
The paper analyses how the discourses of a commodity, trade, and shop become, on the one hand, the subjects of literary reflection and, on the other hand, the certain structures of meaning that form the existential and cultural practices moulding the commodity into a form of reality, trade as a relationship with reality, and shop as a kind of a reality genre in the modern Lithuanian literature. Although the history of a commodity, trademark, or other related subjects in the Lithuanian literature have not been traced on the paper, it is claimed, more out of the feeling, that a commodity and the phenomena related to it are more likely to appear in the modern literary texts. The feeling is based on the theory of a commodity and the trade as a model of a certain culture; the theory, starting with the works of Karl Marx, explains the transformations of the art creation and reception in accordance with the demand / supply forces that started to determine the processes of the art in the Western culture from the middle of the nineteenth century. The theoretical core of cultural commodification enables to speak about a commodity as a literary top not as a coincidence, but as a process, which came to be discussed and reflected long before the market economy in the last decade of the XXth century, in the “non-commodity” Soviet political system, as the documents of the Lithuanian Association for Writers suggest. The combination of the archival data, the facts of the modern literature, and the theory of cultural commodification detects the evolving discourse of commodification reflection and its character in the Lithuanian literature.
Keywords: commodification reflection; theory of culture; the modern Lithuanian literature